Acaricide resistance in livestock ticks infesting cattle in Africa: Current status and potential mitigation strategies - Githaka, Naftaly W.; Kanduma, Esther G.; Wieland, Barbara; Darghouth, Mohamed A.; Bishop, Richard P. (Current research in parasitology & vector-borne diseases, 2022)
In many African countries, tick control has recently been the responsibility of resource-poor farmers rather than central government veterinary departments. This has led to an increase in acaricide resistance, threatening the welfare of livestock farmers in sub-Saharan Africa. Resistance has evolved to the three classes of acaricides used most extensively in the continent, namely fourth-generation synthetic pyrethroids (SP), organophosphates (OP) and amidines (AM), in virtually all countries in which they have been deployed across the globe. Most current data are derived from research in Australia and Latin America, with the majority of studies on acaricide resistance in Africa performed in South Africa. There is also limited recent research from West Africa and Uganda. These studies confirm that acaricide resistance in cattle ticks is a major problem in Africa. Resistance is most frequently directly assayed in ticks using the larval packet test (LPT) that is endorsed by FAO, but such tests require a specialist tick-rearing laboratory and are relatively time consuming. To date they have only been used on a limited scale in Africa and resistance is often still inferred from tick numbers on animals. Rapid tests for resistance in ticks, would be better than the LPT and are theoretically possible to develop. However, these are not yet available. Resistance can be mitigated through integrated control strategies, comprising a combination of methods, including acaricide class rotation or co-formulations, ethnoveterinary practices, vaccination against ticks and modified land management use by cattle, with the goal of minimising the number of acaricide applications required per year. There are data suggesting that small-scale farmers in Africa are often unaware of the chemical differences between different acaricide brands and use these products at concentrations other than those recommended by the manufacturers, or in incorrect rotations or combinations of the different classes of chemicals on the market. There is an urgent need for a more evidence-based approach to acaricide usage in small-scale livestock systems in Africa, including direct measurements of resistance levels, combined with better education of farmers regarding acaricide products and how they should be deployed for control of livestock ticks. [Display omitted] •Resistance to all fourth-generation acaricides is widespread in cattle ticks and is a major problem in Africa.•Acaricide resistance monitoring through the larval packet tests is mostly absent.•The integration of ethnoveterinary products with synthetic acaricides is a promising strategy.•Strengthening laboratory testing and farmersʼ education can lead to rational acaricide use.